The Impact of Monetary Policy on Stock Price Index Movement - Sasongko, Ghalih; Athoillah, Moh. (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study aims to analyze the impact and effectiveness of monetary policy on the decline of the Composite Stock Price Index (IHSG) during the COVID-19 pandemic. The research employs a quantitative approach using Ordinary Least Squares (OLS) with equations 2017-2024 to evaluate the relationship between monthly IHSG and variables such as BI Rate and Exchange Rate. The findings reveal that IHSG significantly affects JUB, con-sistent with previous research indicating that monetary expansion by Bank Indonesia en-hances market liquidity and raises IHSG. However,during the pandemic, global uncertainty disrupted the relationship between IHSG and other economic variables, as evidenced by the insignificance of IHSG concerning BI Rate andthe significant impact of Exchange Rate in the first equation, and Dow Jones in the second. The significant influence of Dow Jones on IHSG highlights global market integration and its effect on investor sentiment in Indonesia. The study emphasizes the importance of understanding the relationship be-tween IHSG and economic variables amid global uncertainty.